96.1k views
4 votes
I can’t answer this question

I can’t answer this question-example-1
User Groksrc
by
4.7k points

2 Answers

5 votes

Answer: The answer is 3

Explanation:

User Udesh
by
4.4k points
1 vote

9514 1404 393

Answer:

3

Explanation:

The radicals get in the way a bit, so we can define ...

x = √p

y = √q

Then the equation is ...

(x +y)/(1-x) = (4x+y)/(1-x^2)

Multiplying by (1-x^2), we have ...

(x +y)(1 +x) = 4x +y . . . . . . using 1-x^2 = (1-x)(1+x) the 1-x factor cancels

x^2 +xy +x +y = 4x +y . . . eliminate parentheses

x(x +y) = 3x . . . . . . . subtract (x+y)

x +y = 3 . . . . . . . . . . divide by x

This is the sum we're looking for:

√p +√q = 3

User Chris Clower
by
5.2k points